Identification of new oral dosing regimens for the neuraminidase inhibitor oseltamivir in patients with moderate and severe renal impairment. Issue 5 (2nd July 2015) - Kamal, Mohamed A.; Brennan, Barbara J.; Subramoney, Vishak; Lien, Yi Ting (Kayla); Morcos, Peter N.; Frey, Nicolas; Rayner, Craig R.
Abstract Availability of lower‐dose oseltamivir capsules, an increased pharmacokinetic database, and a desire to align drug exposure across the spectrum of renal function prompted reassessment of oral dosing in patients with renal impairment. The data set comprised 128 subjects (71 with varying degrees of renal impairment) from 8 studies, which included single and multiple doses of 20–1000 mg. Pharmacokinetic profiles of oseltamivir phosphate (OP) and oseltamivir carboxylate (OC) were modeled simultaneously in NONMEM. Exposure metrics of OP and OC (AUC48 h, Cmax, Cmin) after administration of various dosing regimens were simulated for renal impairment subgroups and compared with exposures in patients with normal renal function receiving approved regimens. For influenza treatment, 30 mg once‐daily and twice‐daily regimens were selected for severe and moderate impairment, respectively. These regimens provided OC exposures similar or above those of the approved 75‐mg twice‐daily treatment regimen in subjects with normal renal function. For influenza prophylaxis, 30 mg once every other day and once‐daily regimens were selected for severe and moderate impairment, respectively. No dosing adjustments were required for mild impairment. This analysis supported revised labeling in the United States and Europe for oral oseltamivir dosing in patients with moderate and severe renal impairment.